2018
DOI: 10.1002/osp4.275
|View full text |Cite
|
Sign up to set email alerts
|

What is known about consumer nutrition environments in Australia? A scoping review of the literature

Abstract: SummaryObjectiveFood environments can influence food selection and hold the potential to reduce obesity, non‐communicable diseases and their inequalities. ‘Consumer nutrition environments’ describe what consumers encounter within a food retail outlet, including products, price, promotion and placement. This study aimed to summarize the attributes that have been examined in existing peer‐reviewed studies of Australian consumer nutrition environments, identify knowledge gaps and provide recommendations for futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 100 publications
(284 reference statements)
0
10
0
Order By: Relevance
“…The only foods excluded from analysis were infant formula, infant food, baking ingredients, culinary condiments, plain coffee, and tea, as the HSR cannot usefully guide selection of these items. The HSR system is currently undergoing a five-year review, and one of the areas of consideration is the foods it should appear on [ 68 ]. Given an automatic five-star rating currently applies to packaged water [ 58 ], which is a product not required to carry nutrition information [ 69 ], and the fact that supermarkets are currently displaying the HSR on selected fresh whole foods such as meat, it is logical to encourage its use across packaged whole foods, especially the nutritious foods recommended in the AGTHE [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only foods excluded from analysis were infant formula, infant food, baking ingredients, culinary condiments, plain coffee, and tea, as the HSR cannot usefully guide selection of these items. The HSR system is currently undergoing a five-year review, and one of the areas of consideration is the foods it should appear on [ 68 ]. Given an automatic five-star rating currently applies to packaged water [ 58 ], which is a product not required to carry nutrition information [ 69 ], and the fact that supermarkets are currently displaying the HSR on selected fresh whole foods such as meat, it is logical to encourage its use across packaged whole foods, especially the nutritious foods recommended in the AGTHE [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient-poor and ultra-processed SOBF were more likely to include the HSR on the front-of-pack than nutritious foods, and many achieved HSR scores of 2.5 stars and over, inaccurately indicating they were a healthy choice. These findings are likely to reflect flaws inherent in the system which are currently being considered in a five-year review [ 68 ], rather than supermarket decision-making per se . Decisions made by the HSR advisory committee to exclude foods such as packaged fruit, vegetables, meat, and fish from the expectation of HSR labelling, but assign an automatic five stars to packaged water [ 58 ], means the recommendations of the Australian Dietary Guidelines [ 12 ] are not promoted consistently.…”
Section: Discussionmentioning
confidence: 99%
“…The consumer nutrition environment (the surroundings, opportunities and conditions that consumers encounter in a food retail outlet, including the physical, economic, policy and socio-cultural environments) is recognised as a major factor influencing dietary choices (6) . Initiatives within the consumer nutrition environment are subsequently of interest to policy makers to reduce unhealthy beverage consumption among Australians and mitigate poor diet as a risk factor for the development of non-communicable diseases (7) .…”
Section: Introductionmentioning
confidence: 99%
“…The novelty of the present study lies in the description of food advertising inside food stores, evidence that is largely scarce in the literature (12,14) and especially in Latin America, where studies of the consumer food environment focus on evaluating and classifying food stores as healthy or unhealthy based on types of foods found in the stores (31) .…”
Section: Discussionmentioning
confidence: 99%
“…only food items that are present within a food store are advertised (11) . Food advertising within food outlets involves messages on packaging or signage, shelf labelling, and product samples and is a dimension of the consumer food environment that is little investigated (12,13) . A systematic review of fifty-six primary, quantitative and observational studies, published from 2000 to 2011, concluded that none of the studies mentioned advertising within food retail outlets and the influence of marketing strategies on an individual's food choices (14) .…”
Section: Introductionmentioning
confidence: 99%